Health Locus of Control and Health Seeking Behaviour. The Ghanaian Experience - Isaac Acheampong Sarfo; Victoria A. Acquaye (Centre for Behaviour and Wellness Advocacy, 2016)
This study sought to examine the relationship between health locus of control orientation and health seeking behaviour, using the Ghanaian experience as a case in point. The study used the general population in the new Juaben Municipality as respondents based on their multiethnic backgrounds. Findings revealed that health locus of control did not mediate significantly between their illnesses and respective health seeking behaviour. There were various sociocultural factors like the collectivist cultural system that made a categorization of locus of control of any individual quite difficult. It was concluded that the cultural practices of respondents were the major determinant of individual's behavior. In addition, the health system as practiced over a long period of time did not allow enough room for patients to make choices in terms of illness behaviour, a situation that affected their health locus of control behaviour.